Role of collagen in oral and systemic diseases - Amol Jain; Kshama Chandurkar; Rohit Jaiswal (Wolters Kluwer Medknow Publications, 2019)
Collagen has been studied appreciably by a massive variety of researchers since 20th century. It is the most important fibrous glycoprotein among the ground substances and forms the core component within the connective tissue structures such as tendons, cartilage, the organic matrix of bone, and cornea, and they retain the muscularity and firmness of these elements. It has triple helices architecture. The collagen family so far has identified 20 different forms. All types of collagens play a role by synthesizing fibers and network of microfibers present in the ground substance, basal lamina also remaining constituents of the matrix. In this review we discuss about the organisation and role of different collagen forms in various tissues. It presents the fundamental structure, synthesis and the different disorders or syndromes which occur due to the defects in the collagen biosynthesis.